A classical book and its content: masā’il al-muhtadī li İkhwānil mubtadī (the guide for the right path for beginners) - Özay, Mehmet (ISTAC-IIUM Publications, 2023)
Studying Islamic sciences in a pesantren entails that junior students possess some fundamental knowledge before continuing towards higher levels in traditional education centres. This level of fundamental knowledge is important for the students’ scholarly career even though it is very basic and consists of relatively simply written books. Masail al Muhtadi li Ikhwanil Mubtadi is a symbolically signifi cant text and was analysed regarding the methods it encourages and its impact on student development.2 The encouragement of characteristic methods such as Question and Answer makes this book unique and signifi cant. In this study, the author of this paper concentrated on the methods used in this book and how they encourage critical thinking. Although critical thinking is a novel concept introduced around the 1980s onwards in Western countries and is currently very popular even in developing countries, due to globalisation, this concept of “critical thinking” can already be found in the traditional education system.